2009
DOI: 10.1002/mc.20535
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 3p12.3‐pcen region associated with tumor suppression in a novel ovarian cancer cell line model genetically modified by chromosome 3 fragment transfer

Abstract: The genetic analysis of nontumorigenic radiation hybrids generated by transfer of chromosome 3 fragments into the tumorigenic OV-90 ovarian cancer cell line identified the 3p12.3-pcen region as a candidate tumor suppressor gene (TSG) locus. In the present study, polymorphic microsatellite repeat analysis of the hybrids further defined the 3p12.3-pcen interval to a 16.1 Mb common region containing 12 known or hypothetical genes: 3ptel-ROBO2-ROBO1-GBE1-CADM2-VGLL3-CHMP2B-POU1F1-HTR1F-CGGBP1-ZNF654-C3orf38-EPHA3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 84 publications
5
52
0
Order By: Relevance
“…2B). As the same batch of cDNAs were used in the semi-quantitative RT-PCR analyses, the expression profiles likely reflect differential expression of RHBDF2 and CYGB in ovarian tumour samples as has been observed in our previous studies with other genes (22,32,34,41,53,54). RHBDF2 and CYGB expression was also detectable in whole ovary, testes and placenta.…”
Section: Defining the 17q25 Tsg Locussupporting
confidence: 65%
See 2 more Smart Citations
“…2B). As the same batch of cDNAs were used in the semi-quantitative RT-PCR analyses, the expression profiles likely reflect differential expression of RHBDF2 and CYGB in ovarian tumour samples as has been observed in our previous studies with other genes (22,32,34,41,53,54). RHBDF2 and CYGB expression was also detectable in whole ovary, testes and placenta.…”
Section: Defining the 17q25 Tsg Locussupporting
confidence: 65%
“…However, in contrast to TOV-81D, TOV-2223G retains some in vitro features of tumourigenic cells, such as the ability to invade matrigel and form colonies in soft agarose (37). By semi-quantitative RT-PCR or gene expression microarray analyses, TOV-81D has also been shown to retain gene expression profiles that resembled NOSE samples (22,32,34,41,53,54). Notably, TOV-81D exhibited the highest level of expression of RHBDF2 whereas low or undetectable levels of expression were observed in all of the other EOC cell lines (Fig.…”
Section: Defining the 17q25 Tsg Locusmentioning
confidence: 99%
See 1 more Smart Citation
“…CHMP2B belongs to the chromatin-modifying protein/charged multivesicular body protein family. In addition, the 3p12.3-pcen region has been identified as a locus harboring candidate to a tumor suppressor gene [14]. However, the same SNP rs2660753 on chromosome 3 was not correlated with PC in Chinese patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…CADM2 gene expression was high in ovarian cancer [25], prostate cancer [26], and lymphoma and melanoma [27,28]. It was recently, reported that CADM2 suppressed the growth of prostate cancer cells [26].…”
Section: Introductionmentioning
confidence: 99%